CHAPPS (chambering application solutions) - Ikhsan, Muhammad Izwan; Matah, Lenny James; Ku Yusof, Ku Mohd Amir Aizat; Salleh, Rafidah@Malissa (Universiti Teknologi MARA, Kedah, 2023)
Chambering Application Solutions (CHAPPS) caters the need of law graduates to apply for pupillage with legal firms. Currently, they need to manually apply to the respective law firm via email, phone call, letter or personally present themselves at the firm. Therefore, CHAPPS website aims to be a onestop platform for law graduates to apply for pupillage. CHAPPS provides the applicants a comprehensive list of law firms where they can apply for pupillage in one single website. They only need to fill in their details before submitting their applications. They can choose the relevant law firms according to their preference in terms of localities and areas of practice. This webpage allows them to search for the law firms alphabetically, by areas of practice and localities, and apply for pupilage directly from the website. This CHAPPS website, therefore, not only may facilitate law graduates’ access to apply for pupillage but also can saves the applicants’ and law firms’ time, resources, and costs.This CHAPPS website uses simple-web based model (Small Scale Website Development Model) in itsdesign and development.